REKONFIGURASI JARINGAN DISTRIBUSI PADA PENYULANG RUMAH SAKIT BALI MED (RSBM) - Nadi Arta, I Gede; Setiawan, I Nyoman; Arta Wijaya, I Wayan (Jurnal SPEKTRUM, 2019)
RSBM feeder is one of the feeders sourced from transformer 2 of the Amlapura Substation. This feeder is a radial type 20 kV distribution network configuration with 133 distribution transformers with a total power of 5.428 kVA and a load of 144 amperes. The lowest voltage condition in RSBM feeders has reached 18,608 kV or a voltage drop of 6.96%. To overcome the voltage drop and power loss in RSBM feeders, it is necessary to reconfigure the network. Network reconfiguration is done by planning a new feeder (Rendang feeder). Analysis of power loss and voltage drop using the help of ETAP software. Based on studies that have been done, before the network reconfiguration is obtained the percentage of voltage drop is 6,98% and the power loss is 5,68%. After being reconfigured with a new feeder plan (Rendang feeder), it showed good results, ie the percentage of voltage drop dropped to 2.09% and the power loss dropped to 3.20%. Whereas the Rendang feeder showed good results with the percentage of voltage drop of 2.78% and the power loss of 3.47%. Based on load forecasting for the next 5 years on RSBM feeders the voltage drop and power loss are still according to the standard. Whereas the Rendang feeder occurs a voltage drop and a power loss that is not up to standard in 2023, namely a voltage drop of 5.20% and a power loss of 5.07%. So that for the Rendang feeder in 2023 it is necessary to break the load or reconfigure the feeder again.